The Obstacles Of English Learning Toward Students’ Achievement - Rakhmyta, Yunie Amalia; Handayani, Julisa (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2022)
This study describes the obstacles in English learning at SMA N 2 Takengon. The location of this school is close to the city and all access to be able to develop students' English skills, but this school does not stand out in the English language arena, therefore the specific objectives of this study is knowing the obstacles faced by students in English learning. This study is qualitative study with an explorative approach. The subjects of this study consisted of nine students who were selected using a purposive sampling technique. Data collection techniques using observation, interviews, and documentation. After that, the data obtained are classified according to Ayu Lestari's theory to determine the obstacle, then the data were analyzed using the theory of Miles and Hubeman, there are; data reduction, data presentation and conclusion drawing/verification. The results of the study is the obstacles faced by students in learning English have two aspects, the first is external; the school does not have a language laboratory, the school library does not provide English reading books such as novels, comics and dictionaries, the school does not have slogans and wall stickers in English. Second is internal; students are not confident in speaking English during English lessons, students are not used to watching movies and reading English books. At the end of the study, it was found that the obstacles faced by students at SMA N 2 Takengon.